Systematic Literature Review: The Role of Educational Toys (APE) in the Development of Early Childhood Development Aspects - Ayu Ernanda, Wilda; Ismaniar, Ismaniar (Universitas Negeri Padang, 2025)
This research is motivated by the suboptimal utilization of Educational Play Tools (APE) in Early Childhood Education (PAUD) institutions, which results in less than optimal stimulation of child developmental aspects. The purpose of this study is to systematically examine research results related to the role and effectiveness of APE in developing cognitive, social-emotional, language, and motor skills in early childhood. This study uses the Systematic Literature Review method by examining scientific sources from reputable journals over the past five years. Data were collected through literature searches and analyzed using content analysis techniques. The results show that the success of APE use is greatly influenced by the role of teachers and their integration into the learning curriculum, not solely by the type or form of play tools used